Pr-doped NiFeOOH catalyst for oxygen evolution reaction and preparation method and application thereof

CN122918618APending Publication Date: 2026-10-16JIANGSU OCEAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611018749.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0009]针对现有技术中稀土掺杂OER催化剂未能同时满足LOM机制热力学、动力学和自旋匹配三重需求的技术空白,本发明提供一种Pr掺杂的NiFeOOH析氧反应催化剂及其制备方法和应用

Benefits of technology

[0032] 1. This invention proposes and verifies Pr 3+ The dual electronic regulation mechanism: on the one hand, Pr 3+ The weak covalent nature of Pr raises the O-2p band center to near the Fermi level, reducing the oxygen vacancy formation energy and satisfying the thermodynamic premise of LOM; on the other hand, Pr 3+ The 4f spin polarization is transmitted through a Pr-O-TM bridge, inducing spin quenching at the Ni site and spin amplification at the Fe site. This asymmetric spin reconstruction lowers the LMCT activation energy and establishes a spin-matching channel conducive to triplet oxygen formation. This invention achieves the simultaneous fulfillment of the triple requirements of LOM with a single dopant element.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918618A_ABST
    Figure CN122918618A_ABST
Patent Text Reader

Abstract

This invention discloses a Pr-doped NiFeOOH oxygen evolution reaction catalyst, its preparation method, and its application, belonging to the field of electrocatalytic materials technology. In the catalyst, Pr is used as Pr 3+ Form exists, Pr 3+ The catalyst possesses a weakly covalent structure and a 4f spin-polarized structure. The weakly covalent structure raises the O-2p band center, while the 4f spin-polarized structure induces asymmetric spin reconstruction at Ni and Fe sites. The catalyst has active sites for catalyzing the oxygen evolution reaction via a lattice oxygen mechanism. The catalyst preparation method includes: immersing a pretreated foamed iron-nickel substrate in a precursor solution containing Pr salt, urea, and NH4F, performing a hydrothermal reaction at 160–190 °C for 10–14 hours, followed by washing and drying. The catalyst reacts in 1M KOH solution at 10 mA cm⁻¹. ‑2 The oxygen evolution overpotential is ≤200mV, and the Tafel slope is ≤40mV. ‑1 And at 500mA cm ‑2 It can operate stably for ≥200 hours with a Faraday efficiency of ≥97% and can be used for alkaline water electrolysis oxygen evolution reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalytic materials technology, specifically relating to a Pr-doped NiFeOOH oxygen evolution reaction catalyst, its preparation method, and its application. Background Technology

[0002] Hydrogen energy, due to its high energy density and clean combustion products, is considered a key carrier for building a sustainable energy system. Electrolysis of water to produce hydrogen is an important pathway to achieve large-scale application of green hydrogen energy. In the water electrolysis process, the oxygen evolution reaction (OER) at the anolyte involves a four-electron-proton coupling process, which has slow reaction kinetics and is a key bottleneck restricting overall energy efficiency.

[0003] Transition metal hydroxyl oxides (MOOHs), particularly NiFeOOH, are considered promising non-noble metal OER catalysts due to their high catalytic activity. However, under the traditional adsorbate evolution mechanism (AEM), the OER performance of NiFeOOH is fundamentally limited by the universal adsorption scaling relationship among the *OH, *O, and *OOH intermediates, making it difficult to break through the theoretical overpotential limit. Activating lattice oxygen to participate in the reaction and switching the reaction pathway to a lattice oxygen-mediated mechanism (LOM) is an effective strategy to overcome the limitations of the AEM scaling relationship.

[0004] However, achieving efficient LOM catalysis requires simultaneously satisfying three interrelated requirements: (1) thermodynamically, the O-2p band must be raised from the deep valence band to near the Fermi level to provide the thermodynamic prerequisite for lattice oxygen to participate in the reaction; (2) kinetics require an efficient ligand-to-metal charge transfer (LMCT) process; and (3) spin matching requires a spin configuration that favors the formation of triplet oxygen (O2). Meeting these three requirements simultaneously is a key challenge in designing efficient LOM catalysts.

[0005] In recent years, rare earth elements have attracted attention in OER catalyst design due to their unique 4f electronic structure. Reported rare earth doping strategies include: inducing lattice distortion through the large ionic radius of rare earth elements to control the d-band center (CN118326438A); utilizing the 4f orbital as an "electronic buffer band" to control metal-oxygen bond properties (CN117512661A); and constructing high-entropy structures with rare earth elements to induce oxygen octahedral distortion (CN121651447A). However, these strategies limit the understanding of the role of rare earth elements to single-dimensional electronic structure manipulation and do not involve the manipulation of spin degrees of freedom.

[0006] While reported Pr-doped NiFe-LDH catalysts (Lei et al., Dalton Transactions, 2026, 55, 2071-2079) have confirmed that Pr doping can enhance OER activity, their mechanism explanation is still limited to the d-band center regulation under the traditional AEM framework and does not involve the LOM pathway.

[0007] Therefore, developing a catalyst that can simultaneously meet the triple requirements of LOM thermodynamics, kinetics, and spin matching through a single doping element is a technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0008] (I) Purpose of the Invention

[0009] To address the technological gap in existing rare-earth-doped OER catalysts that fail to simultaneously meet the thermodynamic, kinetic, and spin-matching requirements of the LOM mechanism, this invention provides a Pr-doped NiFeOOH oxygen evolution reaction catalyst, its preparation method, and its application.

[0010] This invention uses Pr 3+ The weak covalent nature and 4f spin polarization of the dual electronic modulation simultaneously achieve O-2p band lifting, LMCT activation energy reduction and spin matching channel establishment, thereby switching the reaction pathway from AEM to LOM.

[0011] The present invention also provides a method for preparing the catalyst and its application in the oxygen evolution reaction of water electrolysis.

[0012] (II) Technical Solution

[0013] To achieve the above objectives, the present invention adopts the following technical solution:

[0014] 1. A Pr-doped NiFeOOH oxygen evolution reaction catalyst, Pr 3+ It possesses a weakly covalent structure, which raises the O-2p band center to near the Fermi level; Pr 3+ It also has a 4f spin polarization structure, which induces asymmetric spin reconstruction at Ni and Fe sites; the catalyst has active sites for catalyzing oxygen evolution reaction via lattice oxygen mechanism.

[0015] In this invention, the "weakly covalent structure" refers to Pr 3+ After replacing the Ni / Fe sites, Pr 3+ The hybridization between the empty 5d orbital and the O-2p orbital is lower than that between Ni / Fe-3d and O-2p, making the covalentity of the Pr-O bond weaker than that of the Ni-O and Fe-O bonds in their electronic structure states.

[0016] In this invention, the "4f spin polarization structure" refers to Pr 3+ The 4f electrons generate unpaired spin density due to strong electron correlation effects, and transmit spin information to the adjacent transition metal sites through the Pr-O-TM bridge, which is the electronic structure state.

[0017] In this invention, the "asymmetric spin reconstruction" refers to Pr 3+ After the 4f spin polarization is transmitted through the Pr-O-TM bridge, different spin density changes occur at the Ni and Fe sites, with the spin density decreasing at the Ni site and increasing at the Fe site.

[0018] 2. The Pr-doped NiFeOOH oxygen evolution reaction catalyst according to claim 1, wherein the catalyst has the morphology of a two-dimensional nanosheet array grown on a foamed iron-nickel substrate, and Pr is used as Pr 3+ It exists in the form of Pr, with a doping level of 1–15 at%.

[0019] 3. The Pr-doped NiFeOOH oxygen evolution reaction catalyst according to claim 1 or 2, tested in 1M KOH solution at room temperature with a scan rate of 5 mV / s, after iR compensation, the catalyst at 10 mA cm⁻¹ -2 The oxygen evolution reaction overpotential at the current density is no higher than 200 mV, and the Tafel slope is no higher than 40 mV. -1 .

[0020] 4. The Pr-doped NiFeOOH oxygen evolution reaction catalyst according to claim 1 or 2, in 1M KOH solution at room temperature, the catalyst at 500 mA cm⁻¹ -2 The catalyst can operate stably for at least 200 hours at a given current density, with a Faraday efficiency of at least 97%; the dissolution rates of Ni, Fe, and Pr in the catalyst are all no higher than 1 nmol·h⁻¹. -1 .

[0021] 5. A method for preparing the above-mentioned Pr-doped NiFeOOH oxygen evolution reaction catalyst, comprising the following steps:

[0022] (a) The foamed iron-nickel substrate was ultrasonically cleaned in hydrochloric acid solution, acetone and deionized water in sequence, and then dried for later use.

[0023] (b) Dissolve Pr salt, urea and NH4F in water and stir until homogeneous to form a precursor solution;

[0024] (c) Immerse the foamed iron-nickel substrate treated in step (a) into the precursor solution obtained in step (b);

[0025] (d) Hydrothermal reaction at 160–190°C for 10–14 hours;

[0026] (e) The foamed iron-nickel substrate dissolves Ni and Fe under high-temperature hydrothermal conditions, reacting with Pr in the solution. 3+ They are co-deposited on the surface of the foamed iron-nickel;

[0027] (f) Wash and dry to obtain the Pr-doped NiFeOOH oxygen evolution reaction catalyst.

[0028] 6. The preparation method according to claim 5, wherein the Pr salt in step (b) is Pr(NO3)3·6H2O.

[0029] 7. Application of the above-mentioned Pr-doped NiFeOOH oxygen evolution reaction catalyst in the oxygen evolution reaction of water electrolysis.

[0030] (III) Beneficial Effects

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. This invention proposes and verifies Pr 3+ The dual electronic regulation mechanism: on the one hand, Pr 3+ The weak covalent nature of Pr raises the O-2p band center to near the Fermi level, reducing the oxygen vacancy formation energy and satisfying the thermodynamic premise of LOM; on the other hand, Pr 3+ The 4f spin polarization is transmitted through a Pr-O-TM bridge, inducing spin quenching at the Ni site and spin amplification at the Fe site. This asymmetric spin reconstruction lowers the LMCT activation energy and establishes a spin-matching channel conducive to triplet oxygen formation. This invention achieves the simultaneous fulfillment of the triple requirements of LOM with a single dopant element.

[0033] 2. This invention verifies Pr-doped LOM path switching, including TMA, through a combination of experimental and density functional theory (DFT) calculations. + Multiple independent lines of evidence, including suppression experiments, Operano ATR-FTIR spectroscopy, and DFT free energy calculations.

[0034] 3. The Pr-NiFeOOH catalyst prepared in this invention, in 1M KOH solution, at room temperature, 10 mA cm⁻¹ -2 The overpotential at current density is no higher than 200mV (after iR compensation), and the Tafel slope is no higher than 40mV. -1 .

[0035] 4. The Pr-NiFeOOH catalyst prepared in this invention can withstand 500 mA cm⁻¹. -2It can operate stably for no less than 200 hours at a current density of at least 1000 ppm, with a Faraday efficiency of no less than 97%, and the dissolution rates of Ni, Fe, and Pr are all no higher than 1 nmol·h⁻¹. -1 .

[0036] 5. This invention employs a one-step hydrothermal method to grow a catalyst in situ on a foamed iron-nickel substrate, which is simple to prepare under mild conditions. Attached Figure Description

[0037] Figure 1 This is a SEM image of the Pr-NiFeOOH catalyst of this invention.

[0038] Figure 2 The images show HAADF-STEM images and corresponding elemental distribution diagrams of the Pr-NiFeOOH catalyst of this invention.

[0039] Figure 3 This is an HRTEM image of the Pr-NiFeOOH catalyst of the present invention.

[0040] Figure 4 This is an AFM image of the Pr-NiFeOOH catalyst of this invention.

[0041] Figure 5 The above are XPS comparison spectra of the Pr-NiFeOOH catalyst and undoped NiFeOOH of this invention, where (A) is the Ni 2p high-resolution spectrum, (B) is the Fe 2p high-resolution spectrum, and (C) is the Pr 3d high-resolution spectrum.

[0042] Figure 6 The electrochemical OER performance diagram of the Pr-NiFeOOH catalyst of this invention includes polarization curves, overpotential comparisons, and Tafel curve test results.

[0043] Figure 7 This is a stability diagram of the Pr-NiFeOOH catalyst of the present invention, including a 206-hour chronoamperometry test and a comparison of polarization curves before and after the test.

[0044] Figure 8 The diagram shows the Faraday efficiency of the Pr-NiFeOOH catalyst of this invention at different current densities.

[0045] Figure 9 TMA of the Pr-NiFeOOH catalyst of this invention + Inhibition experiment results.

[0046] Figure 10 This is the operando ATR-FTIR spectrum of the Pr-NiFeOOH catalyst of this invention.

[0047] Figure 11The image shows the EPR spectrum of the Pr-NiFeOOH catalyst of this invention.

[0048] Figure 12 This is the DFT calculation model and LOM path free energy diagram of the Pr-NiFeOOH catalyst of this invention.

[0049] Figure 13 This is a comparison chart of the oxygen vacancy formation energies calculated by DFT for the Pr-NiFeOOH catalyst of this invention.

[0050] Figure 14 This is a comparison diagram of the oxygen band distribution calculated by DFT for the Pr-NiFeOOH catalyst of this invention.

[0051] Figure 15 This is a comparison diagram of the Mulliken population analysis of the DFT calculation of the Pr-NiFeOOH catalyst of this invention. Detailed Implementation

[0052] Example 1

[0053] The preparation method of the Pr-doped NiFeOOH oxygen evolution reaction catalyst is as follows:

[0054] (a) Pretreatment of foamed iron-nickel substrate: The foamed iron-nickel substrate was cut into rectangular pieces of 1cm×1.5cm in size, and then ultrasonically treated in 3M HCl solution for 15 minutes, ultrasonically treated in acetone for 8 minutes, and ultrasonically treated in deionized water for 15 minutes in sequence. It was then vacuum dried at 60℃ for 12 hours for later use.

[0055] (b) Preparation of precursor solution: Dissolve 1 mmol Pr(NO3)3·6H2O, 0.6 g urea and 0.3 g NH4F in 30 mL deionized water and stir magnetically for 30 minutes to form a homogeneous precursor solution.

[0056] (c) Immerse the foamed iron-nickel substrate treated in step (a) into the precursor solution obtained in step (b).

[0057] (d) Hydrothermal reaction: The above system was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel hydrothermal reactor and hydrothermally reacted at 180 °C for 12 hours.

[0058] (e) Post-treatment: After natural cooling to room temperature, the foamed iron-nickel substrate was removed, rinsed repeatedly with deionized water and ethanol, and vacuum dried at 60°C for 12 hours to obtain the Pr-doped NiFeOOH oxygen evolution reaction catalyst.

[0059] According to inductively coupled plasma atomic emission spectrometry, the doping amount of Pr in the Pr-NiFeOOH obtained in Example 1 was 6.47 at, and the atomic ratio of Ni:Fe:Pr was 58.21:35.32:6.47.

[0060] Example 2

[0061] The difference from Example 1 is that the amount of Pr(NO3)3·6H2O used in step (b) is 0.2 mmol. The rest of the preparation methods and parameters are the same as in Example 1.

[0062] According to inductively coupled plasma atomic emission spectrometry (ICP-AES), the doping concentration of Pr in the Pr-NiFeOOH obtained in Example 2 is approximately 1 at%.

[0063] Example 3

[0064] The difference from Example 1 is that the amount of Pr(NO3)3·6H2O used in step (b) is 3 mmol. The rest of the preparation methods and parameters are the same as in Example 1.

[0065] According to inductively coupled plasma atomic emission spectrometry (ICP-AES), the doping content of Pr in the Pr-NiFeOOH obtained in Example 3 was approximately 15 at%.

[0066] Example 4

[0067] The difference from Example 1 is that the hydrothermal reaction temperature in step (d) is 160°C. The rest of the preparation methods and parameters are the same as in Example 1.

[0068] Example 5

[0069] The difference from Example 1 is that the hydrothermal reaction temperature in step (d) is 190°C. The rest of the preparation methods and parameters are the same as in Example 1.

[0070] Comparative Example 1

[0071] The difference from Example 1 is that Pr(NO3)3·6H2O is not added in step (b). The rest of the preparation methods and parameters are the same as in Example 1.

[0072] Comparative Example 2

[0073] 25 mg of commercial RuO2 powder was dispersed in a mixture of 260 μL ethanol, 90 μL Nafion solution (5 wt%), and 650 μL deionized water, and sonicated for 30 minutes to form a uniform ink. 100 μL of the ink was drop-coated onto a foamed nickel-iron substrate in portions and air-dried to obtain the RuO2 / NF control electrode.

[0074] The morphology of the catalyst obtained in Example 1 was observed using scanning electron microscopy. Figure 1 As shown, Pr-NiFeOOH forms a uniform conformal capping layer on a foamed iron-nickel framework, which consists of a densely interconnected network of vertically grown two-dimensional nanosheets.

[0075] The elemental distribution of the catalyst obtained in Example 1 was analyzed using HAADF-STEM and EDS elemental surface distribution analysis. Figure 2 As shown, the Ni, Fe, and Pr signals are uniformly distributed throughout the nanosheet.

[0076] The catalyst obtained in Example 1 was structurally analyzed using high-resolution transmission electron microscopy. Figure 3 As shown, the HRTEM image reveals a sheet-like structure and clear lattice fringes.

[0077] The catalyst obtained in Example 1 was structurally analyzed using atomic force microscopy. Figure 4 As shown, the thickness of the sheet is between 1.0 and 1.5 nanometers.

[0078] The surface chemical states of the catalysts obtained in Example 1 and Comparative Example 1 were analyzed using X-ray photoelectron spectroscopy. Figure 5 As shown, Pr has a significant effect on the shape and peak position of the XPS spectra of Ni and Fe, and the presence of Pr was detected.

[0079] Test Example 1: Electrochemical Performance Test

[0080] Electrochemical tests in Examples 1-5 and Comparative Examples 1-2 were conducted in a standard three-electrode system using 1.0 M KOH electrolyte (pH = 13.86). The working electrode was a self-supporting catalyst (geometric area 1 cm²). 2 The counter electrode was a graphite rod, and the reference electrode was Hg / HgO (1.0 MkOH). All potentials were calibrated and converted to potentials relative to the reversible hydrogen electrode (RHE). The electrochemical performance of Example 1 and Comparative Examples 1-2 is as follows: Figure 6 As shown.

[0081] Before linear sweep voltammetry (LSV) testing, the working electrode is activated by 10 cycles of CV. The LSV test is performed at 5 mV / s. -1 The scan was performed at the specified scan rate, and iR compensation was applied to the test results.

[0082] The results of the oxygen evolution reaction overpotential and Tafel slope obtained from the test are shown in Table 1.

[0083] Table 1. OER performance parameters of Examples 1-5 and Comparative Examples 1-2

[0084]

[0085] Test Example 2: Stability Test

[0086] Long-term stability testing of Example 1 was conducted using the chronoamperometry method. Figure 7As shown, a chronocurrent test was performed at a potential of 1.816V, with an initial current density of 532mA / cm². -2 After 206 hours of continuous operation, the current density remained at 521 mA / cm². -2 The attenuation was only 2.1%. The LSV curve shows that at 100 mA cm⁻¹... -2 The potential increased from 1.529V to 1.542V (an increase of 13mV).

[0087] ICP-OES analysis of the electrolyte (after 206 hours of operation) showed that the dissolution rate of Fe was 0.82 nmol / h. -1 Ni is 0.41 nmol h -1 Pr is 0.42 nmol h -1 .

[0088] Test Example 3: Faraday Efficiency Test

[0089] The Faraday efficiency of Example 1 was determined using a gas collection method. For example... Figure 8 As shown in (A), at 25, 50, 75, and 100 mA / cm² -2 Constant current electrolysis was performed for 30 minutes at various current densities. The oxygen evolved at the anode was collected and its volume measured, and compared with the theoretical oxygen production. The results showed that the volume of oxygen collected in the experiment was in high agreement with the theoretical value across all current density ranges, confirming a Faraday efficiency > 97%.

[0090] Furthermore, at 500mA cm -2 The Faraday efficiency was measured again at the current density. For example... Figure 8 As shown in (B), the test time was 10 minutes, and the gas collection volume was recorded every 2 minutes. The experimental oxygen production was in line with the theoretical value, confirming that the Faraday efficiency was still close to 100%.

[0091] Test Example 4: LOM Path Verification

[0092] (1)TMA + Inhibition experiment: The OER activity of Example 1 and Comparative Example 1 was tested in 1.0 M TMAOH electrolyte. Figure 9 As shown, the OER activity of Example 1 was significantly inhibited to a greater extent than that of Comparative Example 1.

[0093] (2) Operando ATR-FTIR Spectroscopy: The operando ATR-FTIR spectra of Example 1 were collected in 1.0 M KOH with increasing potential. Figure 10 As shown, when the potential rises to 1.30V (vs. RHE), a value of ~1210cm appears. -1 The vibration peak appears at ~1145 cm⁻¹ when the potential rises to 1.45 V (vs. RHE).-1 The peak.

[0094] (3) Temperature-dependent EPR: EPR spectra were collected at different temperatures (120–300 K). For example... Figure 11 As shown, the peak-to-peak linewidth of Example 1 is 22-31% wider than that of Comparative Example 1, and the g-value is 0.14-0.16 higher than that of Comparative Example 1.

[0095] Test Case 5: DFT Calculation

[0096] First-principles DFT calculations were performed using the VASP software package. Electron-ion interactions were described using the PAW method, and electron exchange correlation energies were processed using the GGA-PBE functional. The DFT+U method was used (Ni: 5.5 eV, Fe: 4.3 eV, Pr: 4.0 eV), and van der Waals dispersion correction was performed using Grimme's DFT-D3 scheme. The plane wave cutoff energy was 600 eV, and the Brillouin zone was sampled using a 3×3×1 Monkhorst-Pack k-point grid centered at the Γ-axis. The convergence criterion for structural optimization was that the atomic forces were less than [amount missing]. The energy convergence criterion is 10. -5 eV.

[0097] The computational model uses a single-layer NiFeOOH slab model.

[0098] (1) Calculation of reaction pathway free energy: such as Figure 12 As shown, the barrier for the LOM path potential determination step in Comparative Example 1 is 2.43 eV; the barrier for the LOM path potential determination step in Example 1 is 1.79 eV. The barrier for the AEM path potential determination step in Comparative Example 1 is 1.95 eV; the barrier for the AEM path potential determination step in Example 1 is 2.21 eV.

[0099] (2) Calculation of oxygen vacancy formation energy: such as Figure 13 As shown, the oxygen vacancy formation energy of Example 1 is lower than that of Comparative Example 1.

[0100] (3) Calculation of density of states: such as Figure 14 As shown, the O-2p band center of Example 1 is higher than that of Comparative Example 1.

[0101] (4) Mulliken population analysis: such as Figure 15 As shown, compared with Comparative Example 1, in Example 1, the net 3d spin of Ni site decreased from 1.384 μB to 1.101 μB, the net 3d spin of Fe site increased from 2.784 μB to 3.422 μB, and the bridging oxygen O9 obtained a positive spin of +0.025 μB.

[0102] Industrial Application Prospects

[0103] The Pr-NiFeOOH catalyst provided by this invention has the following advantages:

[0104] (1) Low raw material cost: Pr is a relatively abundant variety of rare earth elements, while Ni and Fe are both abundant elements on Earth, thus avoiding the use of precious metals.

[0105] (2) Simple preparation process: The catalyst is grown directly on a large-area foamed iron-nickel substrate by a one-step hydrothermal method without the need for binders, which is suitable for large-scale production.

[0106] (3) Good adaptability to operating conditions: at 500mA cm -2 It can operate stably for more than 200 hours under industrial-grade current density with a Faraday efficiency of >97%.

[0107] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention's specification and drawings under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A Pr-doped NiFeOOH oxygen evolution reaction catalyst, characterized in that, Pr 3+ It possesses a weakly covalent structure, which raises the O-2p band center to near the Fermi level; Pr 3+ It also has a 4f spin polarization structure, which induces asymmetric spin reconstruction at Ni and Fe sites; the catalyst has active sites for catalyzing oxygen evolution reaction via lattice oxygen mechanism.

2. The Pr-doped NiFeOOH oxygen evolution reaction catalyst according to claim 1, characterized in that, The catalyst has the morphology of a two-dimensional nanosheet array grown on a foamed iron-nickel substrate, with Pr as pr 3+ It exists in the form of Pr, with a doping level of 1–15 at%.

3. The Pr-doped NiFeOOH oxygen evolution reaction catalyst according to claim 1 or 2, characterized in that, In 1M KOH solution at room temperature, the catalyst was tested at a scan rate of 5 mV / s. After iR compensation, the catalyst was measured at 10 mA cm⁻¹. -2 The oxygen evolution reaction overpotential at the current density is no higher than 200 mV, and the Tafel slope is no higher than 40 mV. -1 .

4. The Pr-doped NiFeOOH oxygen evolution reaction catalyst according to claim 1 or 2, characterized in that, In 1M KOH solution at room temperature, the catalyst was subjected to an amplitude of 500 mA cm⁻¹. -2 The catalyst can operate stably for at least 200 hours at a given current density, with a Faraday efficiency of at least 97%; the dissolution rates of Ni, Fe, and Pr in the catalyst are all no higher than 1 nmol·h⁻¹. -1 .

5. A method for preparing a Pr-doped NiFeOOH oxygen evolution reaction catalyst as described in any one of claims 1 to 4, characterized in that, Includes the following steps: (a) The foamed iron-nickel substrate was ultrasonically cleaned in hydrochloric acid solution, acetone and deionized water in sequence, and then dried for later use. (b) Dissolve Pr salt, urea and NH4F in water and stir until homogeneous to form a precursor solution; (c) Immerse the foamed iron-nickel substrate treated in step (a) into the precursor solution obtained in step (b); (d) Hydrothermal reaction at 160–190°C for 10–14 hours; (e) The foamed iron-nickel substrate dissolves Ni and Fe under high-temperature hydrothermal conditions, reacting with Pr in the solution. 3+ They are co-deposited on the surface of the foamed iron-nickel; (f) Wash and dry to obtain the Pr-doped NiFeOOH oxygen evolution reaction catalyst.

6. The preparation method according to claim 5, characterized in that, The Pr salt mentioned in step (b) is Pr(NO3)3·6H2O.

Citation Information

Patent Citations

  • Thulium-doped nickel-iron double-metal hydroxide oxygen evolution reaction catalyst

    CN117512661A

  • Rare earth element regulated transition metal selenide self-supporting oxygen evolution electrode and preparation and application thereof

    CN118326438A

  • A-site high-entropy perovskite oxide with oxygen octahedron distortion and preparation method and application thereof

    CN121651447A